Analisis Faktor Usia Pendidikan dan Paritas yang Mempengaruhi Kepatuhan Kunjungan Antenatal Care (ANC) Pada Ibu Hamil - Sari, Intan; Destiana, Serlly; Agustin, Anggun (JURNAL KESEHATAN TERAPAN, 2025)
potential for unexpected complications. Therefore, optimal monitoring is of utmost importance. The aim of this study is to conduct an in-depth analysis of the factors associated with Antenatal Care (ANC) visits in PALI Regency, with a focus on the working area of Babat Public Health Center (Puskesmas Babat). This study employed an analytical survey design with a cross-sectional approach. The research was conducted at Babat Public Health Center in PALI Regency in February 2025. The population in this study consisted of all postpartum mothers who had their pregnancies checked at Babat Public Health Center in PALI Regency in 2024, totaling 270 individuals. The sampling technique used in this study was total sampling. Thus, the sample included all pregnant women who had antenatal check-ups in 2024 at Babat Public Health Center, totaling 270 individuals. The data used were secondary data obtained from medical records, using a checklist sheet as the research instrument. The dependent variable in this study was antenatal care (ANC) visits by pregnant women, while the independent variables included maternal age, education level, and parity. The Chi-Square statistical test was performed using computerized processing with a significance level of α = 0.05. The conclusion of this study is that there is a significant relationship between maternal age and ANC visits, with a P-value of 0.001, which is less than α = 0.05. Likewise, there is a significant relationship between the mother's level of education and ANC visits, with a P-value of 0.001 < 0.05. There is also a significant relationship between parity and ANC visits, as the P-value of 0.003 is still less than α = 0.05.